Semantic processing of multimedia data for e-government applications. (February 2016) - Amato, Flora; Colace, Francesco; Greco, Luca; Moscato, Vincenzo; Picariello, Antonio
Abstract: Knowledge management has become a challenge for almost all e-government applications where the efficient processing of large amounts of data is still a critical issue. In the last years, semantic techniques have been introduced to improve the full automatic digitalization process of documents, in order to facilitate the access to the information embedded in very large document repositories. In this paper, we present a novel model for multimedia digital documents aiming at improve effectiveness of digitalization activities within an information system supporting e-government organizations. At the best of our knowledge, the proposed model is one of the first attempts to give a single and unified characterization of multimedia documents managed by e-government applications, whereas semantic procedures and multimedia facilities are used for the transformation of unstructured documents into structured information. Furthermore, we define an architecture for the management of multimedia documents "life cycle", which provides advanced functionalities for information extraction, semantic retrieval, indexing, storage, presentation, together with long-term preservation. Preliminary experiments concerning an e-health scenario are finally presented and discussed.